Representing the nation: exploring attitudes towards naturalized foreign football players in China - Sullivan, J.; Ross, T.; Wu, C. (Soccer & Society, 2023)
China has long resisted the naturalization of athletes, decrying foreign mercenaries and emphasizing self-sufficiency. Yet amid rising popular nationalism and hardening attitudes in Chinese foreign relations, the sporting authorities have recently adopted an active naturalization strategy for foreign football players. This article explores how official Chinese positions have evolved on the issue, even as suspicions of foreigners and the system for managing them remains intact. We show how China has sought to control and utilize its engagement with foreigners and present exploratory findings on the attitudes of Chinese fans to football player naturalization. We find that cultural appreciation and support for China are major explanatory factors, while much scepticism remains as to foreign players` motives, behaviours and contribution to longer term development of Chinese football.